Анализ электромагнитной совместимости компонентов радиотехнических систем на основе гибких коммутационных структур - Невлюдова, В. В.; Жарикова, И. В. (Харьковский национальный университет радиоэлектроники, 2015)
The analysis of design requirements for the radio-technical systems components on the basis of flexible printed circuit boards taking into account their electromagnetic compatibility is performed in the article. The basic parasite parameters of multi-layered printed circuit boards are considered and the recommendations on their diminishing are formulated. Also the information of mechanical actions influence on the electromagnetic compatibility of radio-technical modules is presented.
Keywords: электромагнитная совместимость; радиотехническая система; печатная плата